A new cognitive behavioural approach to the treatment of obesity. - Cooper, Z; Fairburn, C (2001)
While behavioural approaches to the management of obesity are often successful in achieving clinically significant weight loss, the weight lost is generally regained. The great majority of patients return to their pre-treatment weight within 3 years. There have been attempts to improve the long-term effectiveness of behavioural treatment but the results have been disappointing. In this paper we suggest that, among other factors, this is because of the neglect of the contribution of cognitive factors to weight regain, and because there is often ambiguity over the goals of treatment. We present a cognitive behavioural analysis of the processes involved in weight regain, and we describe a new cognitive behavioural treatment derived from it. This treatment is designed to minimise the problem of weight regain by addressing psychological obstacles to the acquisition of, and long-term adherence to, effective weight-control behaviour.